Credit Management and Financial Performance of Lending Institutions: A Case Study of Brac Mbale Branch - Nambuya Mercy (Uganda Christian University, 2024)
The efficient management of credit plays a very important role in the financial performance of Lending institutions. This research focuses on exploring the impact of credit analysis, credit risk controls, and credit collection policy on the financial performance of Brac Mbale Branch. The objectives of this study were to assess the effect of credit analysis on the financial performance of the bank, to determine the influence of credit risk controls on financial performance, and to analyze the effects of credit collection policy on financial outcomes. The researcher used a descriptive research design that aims to systematically obtain information to describe a population. It helps answer the what, when, where, and how questions regarding the research problem rather than the why. Data was collected from Brac Mbale Branch, utilizing both qualitative and quantitative research methods. The findings indicate that credit analysis has a positive correlation (r = 0.65) and a regression coefficient (β = 0.48) with financial performance; credit risk controls show a stronger correlation (r = 0.72) and regression coefficient (β = 0.56); and credit collection policy also has a significant correlation (r = 0.69) and regression coefficient (β = 0.52) with financial performance. In conclusion, credit analysis significantly impacts financial performance, and it is recommended to enhance the process by adopting advanced credit scoring models and continuous training for credit officers. Effective credit risk controls are crucial for improving financial performance, and it is recommended to strengthen credit risk management frameworks by incorporating robust risk assessment tools and regular monitoring. An efficient credit collection policy positively affects financial outcomes, and it is recommended to implement stricter credit collection policies and follow-up procedures, and consider adopting technology-driven solutions to streamline the collection process. These insights are expected to not only contribute to academic knowledge but also offer practical recommendations for improving credit management practices within the banking sector.